Um método para captura e compartilhamento de dados abertos no contexto dos sistemas da UFMT - Rodrigues, Fabio Antonio (2022)
There is a large volume of data being generated every moment on the world wide web in the globalized world. Among this data, we have open data which is what can be used and distributed freely by society. Public domain information originated within the scope government data is called open government data. The availability of open data government contributes to increasing the transparency of the state and social participation and control about public institutions, being extremely important for modern democracy. The resources of Information and Communication Technologies together with the internet have contributed to a faster and more comprehensive access to public information than conventional media at both the local level, nationally or internationally. Given this scenario, the Federal University of Mato Grosso as a public institution has the responsibility to create actions for the implementation and promotion of opening of your data in accordance with national laws, but the existence of models was not identified or automated methods for generating open government data in the institutional context. In this sense, this paper presents a methodology for generating open data according to a metaprocess and following a technological approach called Data Extraction, Transformation and Loading with the objective of generating open government data in context of UFMT systems. From a methodological point of view, bibliographic research was used as a method of data collection, having as theoretical framework: tools, models, processes or methods for generating open government data, supporting the theoretical foundation of the method proposed by the author. The proposed method presents a generic solution for enrichment semantic data extracted, and resulting from the method, the application developed generate quality government open data ready for publication in a catalog, using the features of the Pentaho's open source Kettle Data Integration. The method was verified and considered adequate by a focus group composed of several specialists. As a contribution to the work, the case study demonstrated the technical feasibility of the method with the availability of data in an open, structured and understandable format by software agents or humans at the end of the automated process.